ANALISIS HARGA POKOK PRODUKSI, NILAI TAMBAH DAN KEUNTUNGAN AGROINDUSTRI PIE PISANG (STUDI KASUS PADA ADEELLA CAKEâ€™S KOTA BANDAR LAMPUNG) - Fadilah Nur Safitri; Dwi Haryono; Yuliana Saleh (Jurnal Ilmu-Ilmu Agribisnis, 2023)
The purpose of this study was to analyze the cost of production, added value, and profits of Adeella Cake's Banana Pie Agroindustry. Respondents in this study were agroindustry owners and agroindustry employees. The method used in this research is a case study in Adeella Cake's Pisang Pie Agroindustry, Bandar Lampung City. Data collection was conducted in October until November 2022. The analytical method used is the analysis of the cost of production, added value analysis, and profit. The results showed that the cost of production was IDR86,596.49 to IDR86,838.80 per kilogram of banana pie with a banana pie selling price of IDR105,000.00 per kilogram of banana pie with a profit margin of 20%. The added value from banana pie processing has a positive value of IDR21,210.78 in August 2022 and IDR17,461.75 in September 2022. The resulting added value ratio is 34.20% in August 2022 and 28.63% in September 2022, which means banana pie processing is valuable because the resulting percentage is more than zero (NT> 0). The total profit from selling banana pie shows an increase in profit in August 2022 of IDR2,939,479.17 and in September 2022 of IDR3,115,979.17, so this business is profitable.Â Key words: agroindustry, profit, value added